Tumor Necrosis Factor Induces Obliterative Pulmonary Vascular Disease in a Novel Model of Connective Tissue Disease–Associated Pulmonary Arterial Hypertension. Issue 10 (20th August 2020) - Bell, Richard D.; White, R. James; Garcia‐Hernandez, Maria L.; Wu, Emily; Rahimi, Homaira; Marangoni, Roberta G.; Slattery, Pamelia; Duemmel, Stacey; Nuzzo, Marc; Huertas, Nelson; Yee, Min; O'Reilly, Michael A.; et al.
Abstract : Objective: Connective tissue disease (CTD)–associated pulmonary arterial hypertension (PAH) is the second most common etiology of PAH and carries a poor prognosis. Recently, it has been shown that female human tumor necrosis factor (TNF)–transgenic (Tg) mice die of cardiopulmonary disease by 6 months of age. This study was undertaken to characterize this pathophysiology and assess its potential as a novel model of CTD‐PAH. Methods: Histologic analysis was performed on TNF‐Tg and wild‐type (WT) mice to characterize pulmonary vascular and right ventricular (RV) pathology (n = 40 [4–5 mice per group per time point]). Mice underwent right‐sided heart catheterization (n = 29) and micro–computed tomographic angiography (n = 8) to assess vascular disease. Bone marrow chimeric mice (n = 12), and anti‐TNF–treated mice versus placebo‐treated mice (n = 12), were assessed. RNA sequencing was performed on mouse lung tissue (n = 6). Results: TNF‐Tg mice displayed a pulmonary vasculopathy marked by collagen deposition ( P < 0.001) and vascular occlusion ( P < 0.001) with associated RV hypertrophy ( P < 0.001) and severely increased RV systolic pressure (mean ± SD 75.1 ± 19.3 mm Hg versus 26.7 ± 1.7 mm Hg in WT animals; P < 0.0001). TNF‐Tg mice had increased α‐smooth muscle actin (α‐SMA) staining, which corresponded to proliferation and loss of von Willebrand factor (vWF)–positive endothelial cells ( P < 0.01). There was an increase in α‐SMA–positive, vWF‐positive cells ( P < 0.01), implicating endothelial–mesenchymal transition. Bone marrow chimera experiments revealed that mesenchymal but not bone marrow–derived cells are necessary to drive this process. Treatment with anti‐TNF therapy halted the progression of disease. This pathology closely mimics human CTD‐PAH, in which patient lungs demonstrate increased TNF signaling and significant similarities in genomic pathway dysregulation. Conclusion: The TNF‐Tg mouse represents a novel model of CTD‐PAH, recapitulates key disease features, and can serve as a valuable tool for discovery and assessment of therapeutics.